PENERAPAN MODEL PEMBELAJARAN YANG MAMPU UNTUK MENINGKATKAN HASIL BELAJAR KIMIA DAN KARAKTER KOMUNIKATIF SERTA PERCAYA DIRI PADA MATERI KIMIA LARUTAN - Nasution, Mutiara Agustina; Silaban, Ramlan; Muchtar, Zainuddin (Magister Pendidikan IPA, UNCEN, 2013)
The aims of this research is to determine the chemistry instructional model to improve student learning outcomes, communicative and self confidence characterâs for XI grade of senior high school on teaching solution chemistry. The 3 experiment class as a samples were taken by purposive random sampling respectively from 3 units of state senior high school (SMA Negeri) in Medan. These experiment class were taught by various teaching model. The experiment class-1 (Ec-1) taught by direct instruction strategy, experimen class-2 (Ec-2) by problem-based learning without media and experiment class-3 (Ec-3) by problem-based learning using the Internet media. The achievement test about solution chemistry used as instrument to know student outcomes, and quisionary and observation list used as intrument to know how communicative and confidence student characters. The one-way ANOVA in SPSS 19 for windows program used to hypothesis testing at Î± = 0.05 level of significance. The results shows (1) There is a significant differences of students learning outcomes between students which taught by direct instruction model, problem-based learning without media and problem-based learning model using internet media on teaching solution chemistry. (2) There is a significance differences of student communicative character between students which taught by by direct instruction model, problem-based learning without media and problem-based learning model using internet media on teaching solution chemistry. (3) There is a significance differences of student self confidence character between students which taught by by direct instruction model, problem-based learning without media and problem-based learning model using internet media on teaching solution chemistry. (4) There is a significant corelation between student communicative character with student learning outcomes in class who taught by problem-based learning using internet media. (5) There is a significant corelation between self-confident character with student learning outcomes in class who taught by direct instruction, problem-based learning without media and problem-based learning using internet media. Kata Kunci : internet, karakter, komunikatif, pembelajaran berbasis masalah, percaya diri